(х+2)(х-3)(х-5)(х-10)=36 решить уравнение

0 голосов
59 просмотров

(х+2)(х-3)(х-5)(х-10)=36 решить уравнение


Алгебра (75 баллов) | 59 просмотров
Дан 1 ответ
0 голосов
Правильный ответ
(х+2)(х-3)(х-5)(х-10)=36
Раскрываем скобки: первую и четвертую, вторую и третью:
(х²-8х-20)(х²-8х+15)=36
Замена переменной
х²-8х=t
(t-20)(t+15)=36
t²-5t-300-36=0
t²-5t-336=0
D=25+4·336=1369=37²
t=(5-37)/2=-16  или t=(5+37)/2=21
x²-8x=-16
x²-8x+16=0
D=64-64=0
x=4

x²-8x=21
х²-8х-21=0
D=64+84=148=(2√37)²
x=(8-2√37)/2=4-√37  или    х=4+√37

О т в е т.
4-√37; 4; 4+√37.
(414k баллов)
0

x²-8x+16=0 , (x+4)²=0 x+4=0 x=-4.